The International Conference, October 6, 2017. »Health Professionals - Stress, Burnout and Prevention«: Book of Contributions - Rakovec-Felser, Zlatka (2017)
The medical staffs in health service institutions are often required to spend time in intense involvement with other people. Frequently, the staff-client interaction is centred on the client's current problems (physical, psychological, social) and is therefore charged with feelings of pain and suffering, fear, despair, turmoil and anger. The main aim of our meeting is to discuss the consequences of such personal burdens as well as to get a better insight into the background of professional burnout phenomenon in general.  Because a burnout could not be only the result of job characteristics but could appear also as the result of work organization type, social relationships, as well as of some personal characteristics and individual′s life style, too, it is essential to look for the forms of support not only on the individual, but it is necessary to consider also the preventive options at the institutional level.
Keywords: professional burnout; social exchange balance; human well-being